Handbook of game theory with economic applications - Arrow, Kenneth J (Ed.); Intriligator, Michael D (Ed.) (Amsterdam Elsevier, 1992)
The aim of the Handbooks in Economics series is to produce Handbooks for various branches of Economics. Each Handbook provides self contained survey of the current state of branch of the economics Handbook of Game thoery is in two volumes. The first volum
Keywords: GAME THEORY; ECONOMICS; MATHEMATICAL